Violent Radicalization and Post-traumatic Dissociation: Clinical Case of a Young Adolescent Girl Radicalized - Rolling, Julie; Corduan, Guillaume; Roth, Martin; Schroder, Carmen M.; Mengin, Amaury C. (Frontiers in Psychiatry, 2022)
Introduction: Since 2014, the profiles of radicalized individuals have changed with the appearance of radical groups composed of a large proportion of adolescents. Various individual, relational, and social vulnerabilities have been identified as being involved in the radicalization process of adolescents. Among these factors, it appears that early and repeated history of personal and/or family psychotraumatism may constitute factors of vulnerability to violent radicalization. Material and methods: The clinical situation of a 17-year-old woman convicted of 'links with a terrorist group (DAECH)' was recruited from the 130 radicalized young people followed by the teams of the Maison des Adolescents and the Child and Adolescent Psychiatry Service of the University Hospitals of Strasbourg since May 2015. Based on the analysis of this clinical case, we present the hypothesis that post-traumatic antecedents can constitute vulnerability factors to violent radicalization, and that post-traumatic symptoms can be 'used' by recruiters of radical movements at different moments of the radicalization process by reactivating post-traumatic psychic mechanisms, but also, for a smaller number of subjects, by the induction of the trauma (viewing of propaganda videos). Results: We show a possible link between violent radicalization and complex psycho-traumatism with an impact of the reactivation of post-traumatic mechanisms such as (i) the activation of the autonomic nervous system and emotional dysregulation on violent acts, (ii) the activation of dissociation mechanisms (psychic sideration) on indoctrination and violent acts, (iii) the activation of control mechanisms on the search for a strict framework of life and a radical ideology and (iv) relational avoidance on the processes of relational rupture and radical socialization. Thus, we highlight that the radicalisation process can respond to the needs and psychic functioning of psycho-traumatized individuals (channeling tensions, being recognized and active in one's life). Discussion: We discuss the central role of propaganda videos in the activation of the ANS and dissociation, and the self-perpetuating process between these two posttraumatic mechanisms. We also discuss clinical and therapeutic perspectives. Conclusion: Psychotrauma can promote radicalisation due to vulnerability mechanisms. Treatments targeting psychotrauma may be one of the ways to get these young people out of violent radicalisation.